Aktivitas Belajar dan Pemecahan Masalah Matematika Melalui Model Pembelajaran Kooperatif Tipe Jigsaw di Kelas VIII SMP N 1 Koto XI Tarusan - Rahmad, Rahmad; Isnaniah, Isnaniah; Risnawita, Risnawita; Rahmat, Tasnim (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to enable students to develop creativity, ability, and problem-solving power according to their own will. This type of research is pre-experimental research with the Static Group Comparison Design research design. The samples in this study were students of class VIII.3 as the experimental class and VIII.1 as the control class. The instruments in this study were observation sheets of learning activities and problem solving tests. The results of this study obtained a recapitulation of observations of student learning activities showing active criteria with an average of 62.49%, and based on the results of the analysis of student problem solving tests using the t-test and using Minitab software assistance which indicated that H0 was rejected. From the calculation results obtained tcount = 1.812 while ttable = 1.670. By using Minitab software, P-value (0.03) < α (0.05) is obtained. So it can be concluded that "Solving student math problems using the Jigsaw cooperative learning model is better than solving student math problems using conventional learning in class VIII SMPN 1 Koto XI Tarusan".